EFEKTIVITAS SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEMASANGAN REKLAME DI KECAMATAN BAKAUHENI KABUPATEN LAMPUNG SELATAN - Pramazuly, Ayu Nadia; Lestari, Tati (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
This study aims to describe the effectiveness of the Civil Service Police Unit in Controlling the Installation of Billboards in Bakauheni District, South Lampung Regency. The research method used is qualitative research methods. The results of the research are based on five main things as the basis of this research, namely Program Success, Target Success, Satisfaction with Programs, Output and Input Levels, and Achievement of Overall Goals. Suggestions from researchers for the Civil Service Police Unit of South Lampung Regency to pay more attention to the personnel ratio as needed so that it can be ideal with the existing criteria. Then it should be necessary to improve the quality of human resources in the internal Civil Service Police Unit of South Lampung Regency with professional education and training and pay attention to facilities and infrastructure to support the performance of the Civil Service Police Unit. Keywords: effectiveness, Controlling, Billboards